Komponen Atsiri Varian Cengkih “Tuni” dan “Afo” Sebagai Varietas Cengkih Lokal Unggul Asal Kepulauan Maluku - Abdul Karim Kilkoda; Asri Subkhan Mahulette; Muhammad Fajri Aditthia Lating (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2025)
Tuni and Afo cloves from the Maluku Islands are two superior local clove varieties widely known in the global spice trade. Both clove varieties are generally traded in the form of dried flower buds, while trade in the form of essential oil is still limited. Previous research has reported that Tuni cloves have two variants, namely, Tuni-cluster I-a and Tuni-cluster I-b, as well as Afo cloves, which have been identified as having two variants, namely Afo-cluster II-a and Afo-cluster II-b. Until now, the content of all essential components of these two clove varieties has not been widely reported. This study aims to identify the content of critical components in the Tuni and Afo clove variants. The essential oil distillation of all samples used the steam-hydro distillation method, while the distillation oil was analyzed for its essential oil component content using Gas Chromatography-Mass Spectrometry (GC-MS) analysis in the form of Agilent Technologies 7890. The component data from the GC-MS analysis were displayed descriptively, while the heatmap profile of the essential oil component grouping was analyzed using R Stat 3.1.0 software. The analysis results obtained six critical oil components in Tuni-group I-a cloves, nine in Tuni-group I-b cloves, six in Afo-group II-a cloves, and six in Afo-group II-b cloves. Eugenol from the phenylpropanoid fraction was identified as the component with the highest concentration in all samples, followed by caryophyllene from the sesquiterpenoid fraction, and Phenol,2-mthoxy-4-(2-propenyl)-, acetate (eugenol acetate) from the phenylpropanoid fraction.